Influence of laser processing conditions for texturing on ultra-high-molecular-weight-polyethylene (UHMWPE) surface. (September 2019) - Hussain, Muzamil; Sufyan, Muhammad; Abbas, Naseem; Ahmad, Hassaan; Joyia, Farooq Mustafa; Noman, Muhammad; Ahsan, Muhammad Mubashir; Raza, Muhammad Naveed; Razaq, Ahsan; Zulqernain, Muhammad; Ullah, Habib; Atif, Muhammad
Abstract: Surface modification of Ultra-High Molecular Weight Polyethylene (UHMWPE) for improving tribological performance is difficult due to its high melt viscosity. Therefore, the potential of laser processing to produce textures on the surface of this material in specific dimensions was evaluated in this study. The influence of several conditions and laser processing parameters was determined. The laser texturing at room temperature, freezing temperature, and producing distilled water layer on UHMWPE disks was not helpful to produce the textures in required dimensions. The textures in specific dimensions were produced at 2 overscan times, 25 mm/s scanning speed and 30 MHz laser intensity using aluminum foil. The coefficient of friction (COF) versus time data under different concentrations of Bovine Serum Albumin (BSA) was recorded for textured and un-textured specimens. The wear performance in term of wear track depth was also compared for textured and un-textured specimens using a confocal microscope.